Preferred and undesirable genotypes of bGH and bIGF-1 genes for the milk yield and quality of black-and-white - Ulyanov, V. A.; Kubekova, B. Z.; Beishova, I.S.; Belaya, A. V.; Papusha, N. V. (My University, 2021)
Background and Aim: The market demand for the quality of milk and dairy products, in particular in terms of such indicators as fat content, the amount and composition of milk protein, etc., is growing. Thus, the need for the selection of dairy herds using genetic markers associated with qualitative traits of milk productivity is becoming urgent. This study aimed to determine the preferred and undesirable genotypes of the AluI polymorphism of the growth hormone gene and SnaBI polymorphism of the insulin-like growth factor-1 gene associated with milk productivity and quality indicators of the black-and-white breed. The genotypes of animals were determined by polymerise chain reaction-restriction fragment length polymorphism (PCR-RFLP). Рыночный спрос на качество молока и молочных продуктов, в частности по таким показателям, как жирность, количество и состав молочного белка и т. Д., Растет. Таким образом, становится актуальной необходимость отбора молочных стад с использованием генетических маркеров, связанных с качественными признаками молочной продуктивности. Это исследование было направлено на определение предпочтительных и нежелательных генотипов полиморфизма AluI гена гормона роста и полиморфизма SnaBI гена инсулиноподобного фактора роста-1, связанных с молочной продуктивностью и качественными показателями черно-пестрой породы. Генотипы животных определяли с помощью полиморфизма длины фрагмента рестрикции цепной реакции (ПЦР-ПДРФ).
VETERINARY WORLD. - 2021.
Keywords: импакт-фактор 2021; генетика животных; кларивате аналитикс; web of science; зарубежное издание; дальнее зарубежье; научный журнал; генотипы крс; зарубежные авторы